Portrayal of Dissociative Identity Disorder Experienced by The Main Character in “Glass” (2019) Movie - Shaney Auryn Putri Aziza; Robby Satria (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This research uses a descriptive qualitative method to analyze the depiction of dissociative identity disorder (DID) experienced by Kevin in the film “Glass”. The purpose of this study is to examine whether Kevin’s portrayal of DID is in accordance with the diagnostic criteria stated by American Psychiatric Association (2013) in its book entitled "Diagnostic and Statistical Manual of Mental Disorders". A descriptive qualitative approach is applied because it allows the researcher to interpret scenes, dialogues, and character behaviors in depth without using numerical data. This method is suitable for film analysis since it focuses on meaning, context, and detailed description, as suggested by Sukmadinata (2011). The data were collected through repeated observation of the film, focusing on scenes that show personality changes, emotional reactions, memory gaps, and interactions with other characters. These scenes were then analyzed by comparing Kevin’s behaviors with the DSM diagnostic criteria for dissociative identity disorder. This process helps identify which symptoms are clearly represented in the film. The results show that Kevin’s character fulfills six out of the seven criteria for dissociative identity disorder. These include the presence of multiple distinct personalities, changes in sense of self and behavior, memory disturbances, depersonalization, distorted perception of reality, and difficulty regulating emotional stress. One criterion, related to significant disruption in relationships or career, was not clearly found. The findings suggest that “Glass” presents a strong representation of DID and can be used as a reference for understanding the disorder in popular media, while also encouraging critical discussion about mental health portrayals in films.